النظام المنسق عالمياً لتصنيف المواد الكيميائية ووسمها (GHS) - United Nations Economic Commission for Europe (United Nations, 2024)
The GHS addresses classification of chemicals by types of hazard and proposes harmonized hazard communication elements, including labels and safety data sheets. It aims at ensuring that information on physical hazards and toxicity from chemicals be available in order to enhance the protection of human health and the environment during the handling, transport and use of these chemicals. It also provides a basis for harmonization of rules and regulations on chemicals at national, regional and worldwide levels, an important factor also for trade facilitation.